2004
DOI: 10.1002/jbm.a.30148
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible hydrogel scaffolds for articular cartilage engineering

Abstract: Articular cartilage has limited potential for repair. Current clinical treatments for articular cartilage damage often result in fibrocartilage and are associated with joint pain and stiffness. To address these concerns, researchers have turned to the engineering of cartilage grafts. Tissue engineering, an emerging field for the functional restoration of articular cartilage and other tissues, is based on the utilization of morphogens, scaffolds, and responding progenitor/stem cells. Because articular cartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 88 publications
1
68
0
Order By: Relevance
“…Moreover, the presence of the fumarate double bonds on PPF can allow for chemical crosslinking, enhancing thus the stability of the hydrogels. Recently, this hydrogel was evaluated for articular cartilage tissue engineering [76]. Chondrocytes were encapsulated in the hydrogel at 37°C and subsequently tested for their phenotypic characteristics.…”
Section: Peg/biodegradable Polyester Copolymersmentioning
confidence: 99%
“…Moreover, the presence of the fumarate double bonds on PPF can allow for chemical crosslinking, enhancing thus the stability of the hydrogels. Recently, this hydrogel was evaluated for articular cartilage tissue engineering [76]. Chondrocytes were encapsulated in the hydrogel at 37°C and subsequently tested for their phenotypic characteristics.…”
Section: Peg/biodegradable Polyester Copolymersmentioning
confidence: 99%
“…The degradation of these polymers can be altered by changing the hydrophilicity through alteration of the chemical structure of the PNI-PAAM. In addition, most pH-sensitive materials mentioned above, including poly( propylene glycol) [160], poly( propylene fumarate) [161], poly(organophosphazenes) [162] and their derivatives, also show temperature-dependent gelation behaviours.…”
Section: Growth Factor Release On Demandmentioning
confidence: 99%
“…A vector of dependent variables {p} [1] is presented to a network of neurons [2] that each possesses a weight vector having the same number of components as the input vector {p}. The norm of the distance between the weight vector for each neuron and the input vector is then calculated (weighted input and net input), and a competitive transfer function [3] outputs 1 for the ''winning neuron,'' the neuron with the most positive net input. The neurons are then updated according to the Kohonen learning rule [4].…”
Section: Figmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Scaffolds have included those that are prefabricated ex situ 4,9,[15][16][17] or those that may be injected, [18][19][20] and they have been formed from a variety of natural and synthetic materials. Several studies have demonstrated that material formulation parameters affect the mechanical properties of these scaffolds as well as their ability to support chondrogenesis by encapsulated or seeded cells.…”
Section: Introductionmentioning
confidence: 99%